Finance sources & conditions for small business (The Corporation BridgetownBB)
Provides small business persons with a guide to various sources of finance available in Barbados. Includes an overview of the various loan, equity, grant, technical assistance and credit guarantee schemes and sets out the basic procedures to be followed when utilising the schemes.
DC